1995
DOI: 10.1021/np50116a029
|View full text |Cite
|
Sign up to set email alerts
|

Xestobergsterol C, a New Pentacyclic Steroid from the Okinawan Marine Sponge Ircinia sp. and Absolute Stereochemistry of Xestobergsterol A

Abstract: A new pentacyclic steroid, xestobergsterol C [1], possessing a cis C/D ring junction, has been isolated together with two known compounds, xestobergsterols A [2] and B [3], from the Okinawan marine sponge Ircinia sp., and the structure determined on the basis of spectral data. Reexamination of the nmr data of xestobergsterols A [2] and B [3] resulted in revision of the configuration at C-23 and of the conformation of ring D in 2 and 3. The absolute stereochemistry of xestobergsterol A [2] was established by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 4 publications
1
38
0
Order By: Relevance
“…As a consequence, the pharmacological potential of contignasterol as a cardiovascular and antiallergic drug could be exploited to treat asthma, allergic rhinitis, psoriasis, rashes, osteoarthritis, hemodynamic disorders involving platelets, hypertension or hypotension, thrombosis and inflammation in general [37]. Xestobergsterol is pentacyclic polyhydroxylated steroid, isolated in 1992 from the Okinawan marine sponge, Xestospongia bergquisita [38]. It inhibits IgE-mediated histamine release from activated mast cells [39], with an inhibitory effect that resulted in being even stronger than some anti-allergy drugs, such as disodium cromoglycate [33].…”
Section: Marine Natural Products: a Potential Immunomodulating Andmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the pharmacological potential of contignasterol as a cardiovascular and antiallergic drug could be exploited to treat asthma, allergic rhinitis, psoriasis, rashes, osteoarthritis, hemodynamic disorders involving platelets, hypertension or hypotension, thrombosis and inflammation in general [37]. Xestobergsterol is pentacyclic polyhydroxylated steroid, isolated in 1992 from the Okinawan marine sponge, Xestospongia bergquisita [38]. It inhibits IgE-mediated histamine release from activated mast cells [39], with an inhibitory effect that resulted in being even stronger than some anti-allergy drugs, such as disodium cromoglycate [33].…”
Section: Marine Natural Products: a Potential Immunomodulating Andmentioning
confidence: 99%
“…It inhibits IgE-mediated histamine release from activated mast cells [39], with an inhibitory effect that resulted in being even stronger than some anti-allergy drugs, such as disodium cromoglycate [33]. In detail, xestobergsterol A blocks the generation of inositol triphosphate (IP3) and phospholipase C (PLC) activity in a dose-dependent way and inhibits early events in IgE-dependent mediator release, such as Ca 2+ -mobilization from intracellular stores [38,39]. Therefore, like contignasterol, it could be considered as a potential anti-asthma agent with a promising pharmacological potential [31].…”
Section: Marine Natural Products: a Potential Immunomodulating Andmentioning
confidence: 99%
“…This pentacyclic polyhidroxylated steroid was isolated in 1992 from the Okinawan marine sponge Xestospongia bergquisita [56]. …”
Section: Biology Of Marine Natural Products: a Potential Anti-inflmentioning
confidence: 99%
“…Stemmin C, stemmosides C, D and G-K are characterized by the unusual presence of a C-17 side chain and no substitution in C-12. On the other hand, stemmosides D-J are also characterized by the occurrence of an uncommon 14 [31][32][33][34][35].…”
Section: Chemistrymentioning
confidence: 99%
“…Therefore a dose dependence study was performed to test the effect on the KS cell proliferation in a concentration range 0.1-20 μM for compounds 27, 31-33, 35, 37-54 and 0.001-0.1 μM for compounds 34 and 36. Results indicated that 15-keto-pregnane glycosides (27,(31)(32)(33)35, and 37-39) and 14,15-secopregnane glycosides (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) reduced the VEGF-induced KS cell proliferation in a dose-dependent manner and the highest reduction occurred at concentration of 10 μM. Between secopregnane glycosides argeloside C showed the highest reduction of the VEGF-induced KS cell proliferation at 10 μM (55.3%), while stemmoside D (SmD) was the most effective both of the pregnane and the secopregnane glycosides showing 65% inhibition of the VEGF-induced cell proliferation at 10 μM (Fig.…”
Section: Biological Activitymentioning
confidence: 99%